Successful containment of two vancomycin-resistant Enterococcus faecium (VRE) outbreaks in a Dutch teaching hospital using environmental sampling and whole-genome sequencing. (May 2021) - Gast, K.B.; van Oudheusden, A.J.G.; Murk, J.L.; Stohr, J.J.J.M.; Buiting, A.G.; Verweij, J.J.
Summary: Background: Vancomycin-resistant enterococci (VRE) may cause nosocomial outbreaks. This article describes all VRE carriers that were identified in 2018 at Elisabeth-Tweesteden Hospital, Tilburg, The Netherlands. Aim: To investigate the genetic relatedness of VRE isolates and the possibility of a common environmental reservoir using environmental sampling and whole-genome sequencing (WGS). Methods: Infection control measures consisted of contact isolation, contact surveys, point prevalence screening, environmental sampling, cleaning and disinfection. VRE isolates were sequenced using a MiSeq sequencer (Illumina, San Diego, CA, USA), and assembled using SPAdes v.3.10.1. A minimal spanning tree and a neighbour joining tree based on allelic diversity of core-genome multi-locus sequence typing and accessory genes were created using Ridom SeqSphere+ software (Ridom GmbH, Münster, Germany). Findings: Over a 1-year period, 19 VRE carriers were identified; of these, 17 were part of two outbreaks. Before environmental cleaning and disinfection, 55 (14%) environmental samples were VRE-positive. Fifty-one isolates (23 patient samples and 28 environmental samples) were available for WGS analysis. Forty-four isolates were assigned to ST117- vanB, five were assigned to ST17- vanB, and two were assigned to ST80- vanB . Isolates from Outbreak 1 ( N =22) and Outbreak 2 ( N =22) belonged to ST117- vanB ; however, WGS showed a different cluster type with 257 allelic differences. Conclusion: WGS of two outbreak strains provided discriminatory information regarding genetic relatedness, and rejected the hypothesis of a common environmental reservoir. A high degree of environmental contamination was associated with higher VRE transmission. Quantification of environmental contamination may reflect the potential for VRE transmission and could therefore support the infection control measures.